Interaction of 3-pyridyland 3-(imidazo[1,2-a]pyridin-2-yl)isocoumarins with hydrazine - Shablykinа О.V.; Krekhovа O.F.; Konovalenkо А.S.; Moskvinа V.S.; Khilyа V.P. (Reports of the National Academy of Sciences of Ukraine, 2018)
The products of 3-pyridyl- and 3-(imidazo[1,2-a]pyridin-2-yl)isocomarins' interaction with hydrazine are investigated. It has been shown that the recyclization of 1H-isochromen-1-one (isocoumarin) cycle to the 2,5-dihydro-1H-benzo[d][1,2]diazepine-1-one system occurs after the addition of a hydrazine molecule to the 3rd position of isocoumarin; and 4-hetaryl-2,5-dihydro-1H-benzo[d][1,2]diazepine-1-ones are recyclized into the corresponding 3-hetaryl-N-aminoisoquinoline-1(2H)-ones under acidic conditions.